Orzekanie w polu polityczności - Mańko, Rafał (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
The purpose of this article is to analyse the relationship between adjudication and the concept of the political. By referring to the understanding of the concept of the political developed inter alia by Carl Schmitt and Chantal Mouffe, the article posits that not all judicial decisions (individual instances of adjudication) should be treated as belonging to the sphere of the political, but only those which fulfil jointly two premises: firstly, they are true decisions, involving at least some degree of discretionality (in the sphere of facts, or in the sphere of law, or in the sphere of the legal classification of facts), and secondly, involving a conflict which is structural for the community or society within which this adjudication is performed. Political adjudication should not be perceived as per se wrong, nonetheless it should be subject to a democratic scrutiny and sustained critique to with greater attention than apolitical adjudication, which merely involves the mechanical application of unambiguous legal rules to undisputed facts.